2021
DOI: 10.3390/ijms221910756
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Human HtrA Family Proteases and Their Distinctive Physiological Roles and Unique Involvement in Diseases, Especially Cancer and Pregnancy Complications

Abstract: The mammalian high temperature requirement A (HtrA) proteins are a family of evolutionarily conserved serine proteases, consisting of four homologs (HtrA1-4) that are involved in many cellular processes such as growth, unfolded protein stress response and programmed cell death. In humans, while HtrA1, 2 and 3 are widely expressed in multiple tissues with variable levels, HtrA4 expression is largely restricted to the placenta with the protein released into maternal circulation during pregnancy. This limited exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 137 publications
0
18
0
Order By: Relevance
“…The HTRA4 gene encodes a human protease that belong to the mammalian high temperature requirement A (HtrA) family. HtrA family proteins are involved in several cellular processes, including apoptosis and unfolded protein stress response [ 33 ]. A recent study suggested that the expression of HTRA4 enhances the effect of chemotherapy in breast and lung cancer cell lines [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The HTRA4 gene encodes a human protease that belong to the mammalian high temperature requirement A (HtrA) family. HtrA family proteins are involved in several cellular processes, including apoptosis and unfolded protein stress response [ 33 ]. A recent study suggested that the expression of HTRA4 enhances the effect of chemotherapy in breast and lung cancer cell lines [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…HTRA2 is an integral member of the HTRA family of serine proteases, which plays an essential role in mitochondrial homeostasis and cell apoptosis (Toyama et al, 2021; Wang & Nie, 2021; Zheng et al, 2021). Hur et al (2019) found that HTRA2 deficiency impaired mitochondrial homeostasis and promoted hepatic fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Given that they are differentially expressed prior to the infection with the virulent strain, they could be promising biomarkers for recovery from virulent ASFV and increased resilience. HTRA3 is part of a highly conserved gene family of serine proteases 33 . GFTP2 controls the ux of glucose into the hexosamine pathway 34 . )…”
Section: Non-recovered Vs Recovered Contrastsmentioning
confidence: 99%